Analisis Pengendalian Kualitas Produk Kopi dengan Metode Seven Tools di Rimoi Kopi - Rusmalah, Rusmalah; Ekaputra Astrawinata, Airlangga (JITMI (Jurnal Ilmiah Teknik dan Manajemen Industri), 2025)
RIMOI KOPI was established as cafe at once manufacturers engaged in the field of food especially of coffee powder. In the production process, there is often a large number of defective products, if this allowed to happen it will result in a loss of consumer trust. Therefore, the aim of quality control is to find out the common ground that causes defective production. This quality control process using Seven Tools method which functions to control the product quality and reduce defective products. The results obtained in this study found two different types of defects in the coffee packaging, such as miscutting and seal damage. From two different types of the defective, it can be seen that seal damage defects are more dominant with higher percentage 86%, while miscutting defects has percentage 72%. The proposed improvements include checking the sealer machine, checking and maintaining machines more regularly, checking and evaluating the methods applied and improving the sealer machine to be able seal the coffee powder packaging and reduce the defective products.